On the Use of Surface Impedance in the Detection and Location of Buried Objects - Akduman, I.; Sahinturk, H.; Yapar, A. (Elsevier BV, 2004)
Summary A method to detect and locate the cylindrical objects buried in a half-space is presented. The method is based on the reconstruction of the appearing surface impedance of the half-space through remote field measurements of scattered field for a single plane wave illumination. The existence of the objects causes surface impedance to be a function of location. The inhomogeneous surface impedance is determined from the boundary condition itself which requires to know the scattered field and its derivative on the boundary. These values are calculated by analytically continuing the measured data to the boundary of the half-space. The method yields satisfactory results if (i) adjacent cylinders are not very close to each other, (ii) the cylinders are not deeply buried and (iii) the half-space of burial is not highly attenuative.